2013
DOI: 10.1155/2013/496913
|View full text |Cite
|
Sign up to set email alerts
|

Skin Cancer Knowledge, Beliefs, Self-Efficacy, and Preventative Behaviors among North Mississippi Landscapers

Abstract: There are slightly over one million workers in the landscape service industry in the US. These workers have potential for high levels of solar ultraviolet radiation exposure, increasing their risk of skin cancer. A cross-sectional sample of 109 landscapers completed a self-administered questionnaire based on Health Belief Model (HBM). The participants correctly answered 67.1% of the knowledge questions, 69.7% believed they were more likely than the average person to get skin cancer, and 87.2% perceived skin ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 28 publications
3
36
0
1
Order By: Relevance
“…This finding is in concordance with previous studies that included other professionals, such as landscapers and dairy farmers (67.1 and 70 %, respectively) [11,12]. While the vast majority (87.4 %) believed that skin cancer is a serious disease, less (42.5 %) believed they would develop skin cancer during their lifetime, and even fewer (35.6 %) believed their risk was higher than average.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…This finding is in concordance with previous studies that included other professionals, such as landscapers and dairy farmers (67.1 and 70 %, respectively) [11,12]. While the vast majority (87.4 %) believed that skin cancer is a serious disease, less (42.5 %) believed they would develop skin cancer during their lifetime, and even fewer (35.6 %) believed their risk was higher than average.…”
Section: Resultssupporting
confidence: 91%
“…It is noteworthy that a substantial number of participants reported ''rarely or never'' wearing long-sleeved shirts (67.8 %), wide-brimmed hats (58.6 %), or sunscreen (60.9 %). The SPB patterns in this study are similar to those reported by outdoor workers in previous studies [11,12]. Collectively, state park workers in the present study showed low levels of SPBs.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In the same study, outdoor workers’ sun‐related knowledge and attitudes were found largely inadequate, with many workers stating that they never or only rarely wore a long‐sleeved shirt (50–80%), sun‐protective headgear (30–80%) and sunscreen (30–100%) while working in the sun. Outdoor workers were generally exposed to UVR during work for two to eight hours which far exceeds recommended guidelines . Additionally, many outdoor workers also spent a substantial time outdoors in their leisure time leaving their skin exposed to high doses of UVR .…”
Section: Discussionmentioning
confidence: 99%